Involvement of a Velvet Protein FgVeA in the Regulation of Asexual Development, Lipid and Secondary Metabolisms and Virulence in Fusarium graminearum - Jiang, Jinhua; Liu, Xin; Yin, Yanni; Ma, Zhonghua (PloS one, 2011)
The velvet protein, VeA, is involved in the regulation of diverse cellular processes. In this study, we explored functions of FgVeA in the wheat head blight pathogen, Fusarium graminearum,using a gene replacement strategy. The FgVEA deletion mutant exhibited a reduction in aerial hyphae formation, hydrophobicity, and deoxynivalenol (DON) biosynthesis. Deletion of FgVEA gene led to an increase in conidial production, but a delay in conidial germination. Pathogencity assays showed that the mutant was impaired in virulence on flowering wheat head. Sensitivity tests to various stresses exhibited that the FgVEA deletion mutant showed increased resistance to osmotic stress and cell wall-damaging agents, but increased sensitivity to iprodione and fludioxonil fungicides. Ultrastructural and histochemical analyses revealed that conidia of FgVeA deletion mutant contained an unusually high number of large lipid droplets, which is in agreement with the observation that the mutant accumulated a higher basal level of glycerol than the wild-type progenitor. Serial analysis of gene expression (SAGE) in the FgVEA mutant confirmed that FgVeA was involved in various cellular processes. Additionally, six proteins interacting with FgVeA were identified by yeast two hybrid assays in current study. These results indicate that FgVeA plays a critical role in a variety of cellular processes in F. graminearum.